2020
DOI: 10.1186/s12888-020-02678-x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between dietary intakes and psychological disorders in Iranian adults: a population-based study

Abstract: Background: Previous studies showed an association between dietary intakes and psychological disorders. This study aimed to assess the association between dietary intakes and psychiatric disorders in Iran. Methods: In this cross sectional research, the data on 9965 adults were extracted from enrollment phase of Yazd Health Study (YaHS); a population-based cohort study on Iranian adults which was conducted during 2014 to 2016. Data on socio-demographic characteristics, tobacco use, history of chronic disease, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
1
20
2
Order By: Relevance
“…Finally, multiple logistic regression analysis was used to evaluate the relation between dietary intake and psychological disorders. However, in this study the main focus was not on PA, it was only included as a confounder [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, multiple logistic regression analysis was used to evaluate the relation between dietary intake and psychological disorders. However, in this study the main focus was not on PA, it was only included as a confounder [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study provided evidence that high-quality plant-based products (avoiding ultra-processed products and ensuring an adequate intake of different nutrients) can be protective for vegans/vegetarians without depression; although, individuals affected by depression did not show that benefit [ 222 ]. Similarly, avoiding the consumption of animal-based products such as meat, eggs, or dairy products did not show an improvement in mental health or MDD, according to some studies and meta-analyses [ 223 , 224 ]. This is attributed to the fact that these natural foods are rich in the different above-mentioned nutrients with potential benefits for the body [ 225 ]; although, vegetarianism/veganism if properly balanced, is also a laudable choice.…”
Section: Translational Opportunities: Clinical Management Of Mdd Thro...mentioning
confidence: 99%
“…However, relevant epidemiological studies remained scarce and inconsistent. One cross-sectional study reported that eating eggs more than once a week might have a beneficial effect on depressive symptoms [ 11 ]. On the contrary, another study demonstrated no significant association between egg intake and depressive symptoms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%